Performance of a spherical high pressure gas TPC for neutrino magnetic moment measurement. (14th March 2023) - Bouet, R.; Busto, J.; Cecchini, V.; Cerna, C.; Charpentier, P.; Dastgheibi-Fard, A.; Druillole, F.; Jollet, C.; Hellmuth, P.; Katsioulas, I.; Knights, P.; Giomataris, I.; et al.
Abstract: The measurement of neutrino magnetic moment larger than 10 -19 μB would be a clear signature of physics beyond the standard model other than the existence of massive Dirac neutrinos. The use of a spherical proportional counter detector filled with gas at 40 bar located near a nuclear reactor would be a simple way to perform such a measurement exploiting the developments made on such a technology for the search of dark matter and neutrinoless double beta decay. Different targets can be used just by replacing the gas: xenon, CF4 and argon were compared and the sensitivity in one year of data taking could reach the level of 4.3 × 10 -12 μB, 6.5 × 10 -12 μB, and 8.5 × 10 -12 μB, respectively.